Peran Guru Akidah Akhlak dalam Menanamkan Keshalehan Sosial Santri di Pondok Pesantren Al-Kahfi Bangun Purba Kabupaten Rokan Hulu - Dwi Restiana; Rabiatul Adawiah; Sarmadhan Lubis; Mhd. Iskandar Lubis; Hesty Febina Pingky (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
Social piety is an important aspect of Islamic education that reflects positive relationships between individuals and their fellow human beings through compassion, mutual aid, responsibility, and respect for others. However, changing times and the influence of the social environment require ongoing guidance so that the values of social piety can be instilled in students. In this regard, Akidah Akhlak teachers play a strategic role as educators, mentors, and role models in shaping students’ social behavior in accordance with Islamic values. This study aims to determine the role of Akidah Akhlak teachers in instilling social piety among students and to identify the supporting and inhibiting factors in the process. This research was conducted at Pondok Pesantren Al-Kahfi Bangun Purba located in Rokan Hulu Regency. This research uses a qualitative method with a descriptive approach. Data were collected through interviews, observations, and documentation. The research subjects consisted of Akidah Akhlak teachers and twelfth-grade students. Data analysis was carried out through data reduction, data presentation, and conclusion drawing. The results of the study show that the role of Akidah Akhlak teachers is very important in instilling social piety among students, namely as educators, mentors, and role models. The values are instilled through lecture methods, discussions, role modeling, and habituation in daily life. Students’ social piety is reflected in helping behavior, responsibility, and concern for others.The supporting factors include a religious school environment, teacher role modeling, school regulations, and social and religious activities. Meanwhile, the inhibiting factors include differences in students’ backgrounds, lack of self-awareness, external environmental influences, and uncontrolled use of technology.Thus, the role of Akidah Akhlak teachers significantly influences the development of students' social piety, although there are still some obstacles that need to be addressed.